The impact of teacher professional development programs on student achievement in rural China: evidence from Shaanxi Province. Issue 2 (3rd April 2019) - Lu, Meichen; Loyalka, Prashant; Shi, Yaojiang; Chang, Fang; Liu, Chengfang; Rozelle, Scott
ABSTRACT: There is a significant gap in academic achievement between rural and urban students in China. Policymakers have sought to close this gap by improving the quality of teaching in rural areas through teacher professional development (PD) programs. However, there is limited evidence on the effectiveness of such programs. In this paper, we evaluate the impact of a PD program-National Teacher Training Program (NTTP)  and find that the NTTP has no effect on math achievement. We also find that while the program has a positive effect on math teaching knowledge of teachers, it has no significant effect on teaching practices in the classroom. Taken together, these results indicate that teachers may have improved their knowledge for teaching from NTTP, but did not apply what they learned to improve teaching practices or student learning.